DEVELOPMENT OF CALLIGRAPHY SCHOOLS AND THE POPULARIZATION OF RASM AL-MUSHAF IN THE KHWARAZMIAN ERA (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes the cultural and academic life during the zenith of the Khwarazmshah state (1077–1231), focusing specifically on the development of calligraphy schools and the crucial role of the discipline Rasm al-Mushaf. The paper reveals how Kunya Urgench became a major intellectual center in the entire Islamic East during the reign of Ala ad-Din Muhammad II, detailing the rulers' active scholarly patronage and the function of scriptoriums (bookmaking workshops) attached to the court.